2000
DOI: 10.1139/x99-185
|View full text |Cite
|
Sign up to set email alerts
|

Light extinction coefficients specific to the understory vegetation of the southern boreal forest, Quebec

Abstract: This study was conducted in six different forest types in Abitibi, Que., (i) to identify the factors that most influence understory light transmission in the southern boreal forest and (ii) to develop light extinction coefficients (k), which could be used to simulate light transmission in the understory. Light availability and understory vegetation (cover, composition, vertical distribution, and leaf area index) were characterized within three strata (0.05-5 m) in a total of 180 quadrats. Calculated k values w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
50
0
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 88 publications
(62 citation statements)
references
References 26 publications
10
50
0
2
Order By: Relevance
“…For instance, Lapointe et al (2006) reported an average light transmission of 7.7% at the same site, for measurements made at 0.75 m above-ground. Messier et al (1998) and Aubin et al (2000) also reported lower light levels than in Brais et al (2004), i.e., on average 9-10% in closed-canopy aspen-dominated stands from the same area. An alternative explanation to the discrepancy between GLI pre and GLI obs is that the simplified representation of tree crowns in SORTIE-ND -with dimensions derived from allometric relations -might have contributed to a possible underestimation of light conditions under closed canopy conditions.…”
Section: Model Evaluationmentioning
confidence: 90%
“…For instance, Lapointe et al (2006) reported an average light transmission of 7.7% at the same site, for measurements made at 0.75 m above-ground. Messier et al (1998) and Aubin et al (2000) also reported lower light levels than in Brais et al (2004), i.e., on average 9-10% in closed-canopy aspen-dominated stands from the same area. An alternative explanation to the discrepancy between GLI pre and GLI obs is that the simplified representation of tree crowns in SORTIE-ND -with dimensions derived from allometric relations -might have contributed to a possible underestimation of light conditions under closed canopy conditions.…”
Section: Model Evaluationmentioning
confidence: 90%
“…The full list of species 247 included in each group is given in Appendix S3. The proportion of bole height (b sp ) 248 and light extinction coefficients (k sp ) for tree and shrub species were inferred from 249 bibliographic sources (Aubin et al, 2000;Bréda, 2003) (Table 1). To determine soil 250 water potentials related to 50% of water conductance loss, species were divided 251 between strongly isohydric (Ψ sp = -2.0 MPa; conifers, beech and 'other trees'), 252 moderately isohydric (Ψ sp = -3.0 MPa; oaks and 'shrubs R+S+'), moderately 253 anisohydric (Ψ sp = -4.0 MPa; 'shrubs R+S-') and strongly anisohydric (Ψ sp = -5.0 254 MPa; 'shrubs R-S+').…”
Section: Study Area and Calibration Of Species-specific Parameters 229mentioning
confidence: 99%
“…Sample sizes are given where appropriate and should be considered when interpreting light measurement results, especially at year 4 where values at 1 m should be used preferably. We computed an understory density index as a function of the light extinction coefficient of that layer [4] …”
Section: Competition and Light Availabilitymentioning
confidence: 99%